Sistem Diagnosis Penyakit Pada Tanaman Melon Menggunakan Metode Forward Chaining - Certainty Factor - Irfan Aprison; Nurul Hidayat; Budi Darma Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Knowledge of melon plants is a must for the cultivators of melon plants, one of the knowledge is the diseases that can attack melon plants. Melon plant disease is one of the obstacles that faced by cultivators of melon plants. However, lack of understanding owned by the cultivators and the unavailability of disease experts in horticultural crops is one of the main factors that hold up the development of agriculture in melon plants. Thus, in melon plant problems can be developed melon plant disease diagnosis system. The method used is Certainty Factor, this method can accommodate uncertainty and describe the level of confidence of an expert against the facts. The melon plant diagnosis system receives input from the user and then the input will be calculated based on the trust level based on the user and the expert. After that, it will be compared with every single disease where the disease has the largest percentage that is believed to attack the melon plant. This research coantains 36 symptoms and 10 types of diseases in melon plants. In testing, this research used validation testing (black box) and accuracy testing. In the validation test obtained functionality level of 100% indicating the system in accordance with the list of needs. The accuracy rate of this system is 80% gain from accuracy test which indicates that this system is able to function well using Certainty Factor.